Structuralism and Substratum. Indo-Europeans and Semites in the Ancient Near East - Szemerényi, Oszvald (1964)
Titel irrtümlich: Aryans; cf. Language 40, Supplement. Bulletin No. 37 (Baltimore 1964) 21: Collitz Lecture.